Modeling the Roles of Heterogeneity, Substitution, and Inventories in the Assessment of Natural Disaster Economic Costs - Hallegatte, Stéphane (World Bank, Washington, DC, 2012)
Based on an IO structure, the ARIO-inventory model simulates the economic consequences and responses to a natural disaster. It represents explicitly production bottlenecks, models a flexibility in production capacity in case of scarcity, and introduces inventories as an additional flexibility in the production system. Moreover, it takes into account the heterogeneity in goods and services within sectors, and the consequences on production bottlenecks and substitution possibilities. The model is applied to the landfall of hurricane Katrina in Louisiana. Sensitivity analyses show that results are extremely sensitive to several uncertain model parameters. In particular, accounting for heterogeneity within sectors has a large negative influence on production bottlenecks, and thus increases total economic losses from natural disasters and other supply-side shocks. This paper shows that current models disregard important mechanisms and proposes an approach to take them into account.